The Drosophila Wilms? Tumor 1-Associating Protein (WTAP) homolog is required for eye development. - Anderson, A.M.; Weasner, B.P.; Weasner, B.M.; Kumar, J.P. (Developmental Biology, 2014)
Sine Oculis (So), the founding member of the SIX family of homeobox transcription factors, binds to sequence specific DNA elements and regulates transcription of downstream target genes. It does so, in part, through the formation of distinct biochemical complexes with Eyes Absent (Eya) and Groucho (Gro). While these complexes play significant roles during development, they do not account for all So-dependent activities in Drosophila. It is thought that additional So-containing complexes make important contributions as well. This contention is supported by the identification of nearly two-dozen additional proteins that complex with So. However, very little is known about the roles that these additional complexes play in development. In this report we have used yeast two-hybrid screens and co-immunoprecipitation assays from Kc167 cells to identify a biochemical complex consisting of So and Fl(2)d, the Drosophila homolog of human Wilms? Tumor 1-Associating Protein (WTAP). We show that Fl(2)d protein is distributed throughout the entire eye-antennal imaginal disc and that loss-of-function mutations lead to perturbations in retinal development. The eye defects are manifested behind the morphogenetic furrow and result in part from increased levels of the pan-neuronal RNA binding protein Embryonic Lethal Abnormal Vision (Elav) and the RUNX class transcription factor Lozenge (Lz). We also provide evidence that So and Fl(2)d interact genetically in the developing eye. Wilms? tumor-1 (WT1), a binding partner of WTAP, is required for normal eye formation in mammals and loss-of-function mutations are associated with some versions of retinoblastoma. In contrast, WTAP and its homologs have not been implicated in eye development. To our knowledge, the results presented in this report are the first description of a role for WTAP in the retina of any seeing animal.